H33 The swallowing disorder in huntington's disease (hd): an observational study – nutritional aspects. (September 2018) - Geitner, Carolin; Schradt, Falk; Lang, Christina; Weydt, Patrick; Lindner-Pfleghar, Beate; Landwehrmeyer, G Bernhard; Werner, Cornelius; Schumann, Beate; Süssmuth, Sigurd; ,
Abstract : Backround: Dysphagia is a common problem in HD. There are limited data on the features of dysphagia observed in HD affecting different phases of ingestion, on the onset and progression of dysphagia in HD including a correlation to other clinical features of HD (motor & cognitive impairment, degree of chorea) and its impact on nutritional status. Aim: The nutritional part of the study aims to establish the relationship between malnutrition and dysphagia. Clinical assessments by speech therapists as well as patient reported data Questionaires Clinical data as well subjective information by Dysphagia affected people in HD, provide data which could give the opportunity to create more exact Nutritional Guidelines for Dysphagia in HD. Methods: 98 subjects with HD and a complaint of subjective swallowing problems were enrolled. 13 subjects we saw twice in process and two subjects three times. 32 participants completed questionnaires on complaints (KSA), quality of life as impacted by swallowing problems (SWAL-QOL) and a nutritional questionnaire (specifically designed for the study) and were studied using the FEES procedure (Fiberoptic endoscopic evaluation of swallowing). Furthermore we collected data on weight, BMI, stage of HD and clinical phenotypical characteristics of HD. Results: 11.7 % of the participants had a BMI indicative of malnutrition. 7.2 % had a BMI indicative of overweight. Correlations were established between the extent of dysphagia and the complaints on KSA, SWAL-QOL and the clinical swallowing assessments as well as the results obtained by FEES. Conclusions: The relationship of BMI and dysphagia is complex. For the future we will collect longitudinal data to investigate the rate of progress of the dysphagia and the course of the nutritional status in HD.